The Effect of Hope and Happiness on the Spiritual Health of Adolescent Girls: A Correlational Study - Mousavi Asl, Seyed Ali; Asghari, Leila (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2025)
Objective:  This study aimed to determine the relationship between happiness and hope with spiritual health among adolescent girls.Methods and Materials: This study aimed to investigate the relationship between happiness and hope with spiritual health in adolescent girls. A descriptive-correlational research design was employed, and a sample of 300 adolescent girls from secondary schools in Tehran was randomly selected. The research instruments included the Oxford Happiness Questionnaire, the Hope Scale, and the Spiritual Health Questionnaire. Data were analyzed using SPSS software, employing Pearson’s correlation coefficient for correlation analysis and stepwise regression analysis for predictive modeling.Findings: The results indicated a significant positive correlation between happiness and hope with spiritual health in adolescent girls. Specifically, hope accounted for 32% of the variance in spiritual health, while happiness explained 26% of the variance. These findings suggest that happiness and hope serve as key factors in promoting adolescents’ spiritual health.Conclusion: Based on these findings, it is recommended that educational and counseling programs in schools focus on fostering adolescents’ happiness and hope to enhance their spiritual health. Furthermore, the results of this study can serve as a foundation for future research exploring the effects of other psychological variables on adolescents’ spiritual health. Given the psychological and social challenges faced by adolescent girls, emphasizing happiness and hope can be considered an effective strategy for improving their quality of life and spiritual well-being.